PENERAPAN SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK REKOMENDASI PENERIMA KREDIT - Julianto Simatupang; Purjumatin Purjumatin (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
In the midst of uncertainty and economic upheaval after the Covid-19 pandemic had an impact on the order of life and the national economy. The community, especially MSME actors who feel the direct impact, have to rack their brains to survive through it. Most of them have to take advantage of credit in order to continue to exist. The banking sector as a provider of credit services is the main target of the community. KSP. Tama Mandiri as one of the banking sector institutions experienced a surge in customers applying for loans. So that at this time they have difficulty in determining customers who are eligible to receive credit. In an effort to optimize service for granting credit, a selection is made based on the criteria of employment, income, number of dependents, status of residence and collateral. This study intends to build a decision support system for selecting credit recipients by applying the Simple Additive Weighting method. This method was chosen because it can carry out a ranking process based on criteria and weights and is able to determine the best alternative. The results of the application are in the form of customer reports and the results of the overall selection of credit recipients as well as recommendations for customers who are most deserving of credit based on the highest preference value.